2015
DOI: 10.1007/s00264-015-2807-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary modular total knee replacement in severe and unstable osteoarthritis. Predictive factors for failure

Abstract: All severe and unstable knees obtained similar and overall excellent-good outcomes and survival using the Optetrak CCK. Although we found that there are some factors that could change the survival of the total knee replacement, these did not change the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
7
1
Order By: Relevance
“…Despite the disadvantages that have been associated with increased constraint, midterm survivorship from revision for aseptic loosening was 100%, which is in line with previous studies of primary CCK that reported no cases of failure of the implants for aseptic loosening at midterm follow-up in primary TKA [13,14,17,19,23,31,33]. Our results compare favorably with those of other studies [11,15,22,[34][35][36][37] (Table 3). No complications related to the tibial post mechanism were reported at a mean follow-up of 9 years (range 6-12 years).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Despite the disadvantages that have been associated with increased constraint, midterm survivorship from revision for aseptic loosening was 100%, which is in line with previous studies of primary CCK that reported no cases of failure of the implants for aseptic loosening at midterm follow-up in primary TKA [13,14,17,19,23,31,33]. Our results compare favorably with those of other studies [11,15,22,[34][35][36][37] (Table 3). No complications related to the tibial post mechanism were reported at a mean follow-up of 9 years (range 6-12 years).…”
Section: Discussionsupporting
confidence: 90%
“…However, multiple studies have reported good short-to-midterm results of CCK implants in primary TKAs. In addition, range-of-motion (ROM) [17], clinical and radiographic outcomes seem to be comparable to standard PS implants in severe coronal deformity and ligamentous laxity [11,12,15,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study reported the 10-year outcomes of 54 primary TKAs (44 patients) receiving CCK of which at least 28 had valgus deformity: the 10-year prosthesis survival rate was 96%; there was only 1 posterior dislocation and 2 patients with implant loosening; no other revision surgeries were reported [4]. A study focusing on valgus TKA also reported 0 dislocation in 105 CCK TKAs in a minimum 7-year follow-up, although there were 2 cases with aseptic loosening [15]. Given the rarity of dislocation following CCK TKA in literature, the dislocations in this series were less likely to be related to the CCK prosthesis per se.…”
Section: Discussionmentioning
confidence: 99%